Clinical and Analytical Verification of an Automated Fecal Calprotectin Immunoassay with Extraction Device. (13th February 2021) - Wyness, Sara P; Lin, Leo; Jensen, Ryan; Bird, Joseph; Norgyal, Tenzin; Jensen, Gabrielle; Johnson, Lisa M
Abstract: Background: Fecal calprotectin (FC) is a screening test for intestinal inflammation, and often used by clinicians to help identify and monitor patients with inflammatory bowel disease (IBD). Improvements in FC assays include moving to more automated immunoassays compared to ELISAs and simple-to-use extraction devices compared to manual weighing for the extraction process. Methods: A method comparison was performed between the PhiCal ELISA and LIAISON immunoassay for 53 stool samples, and the screening results were compared to the gold standard endoscopy with biopsy results. Clinical accuracy was assessed by comparing the FC results from each assay to the presence or absence of inflammation determined from the biopsy report. The performance of the extraction device was compared to manually weighing. Additional studies were completed to verify the manufacturer's claims. Results: The FC results were compared to the biopsy results for detecting inflammation. PhiCal ELISA had a sensitivity of 86% and specificity of 100%, while the LIAISON immunoassay had a sensitivity of 97% with specificity of 94%. Therefore, the LIAISON immunoassay performed better than the PhiCal ELISA. The extraction device performed well compared to manual weighing if stool samples were <800 μg/g, within Bristol stool types 2-6, and did not contain a significant amount of undigested material, fibrous material, or mucus. Conclusion: The LIAISON immunoassay with extraction device has acceptable performance for clinical use in measuring fecal calprotectin.